2013
DOI: 10.1089/ars.2013.5184
|View full text |Cite
|
Sign up to set email alerts
|

Interplay Between Heme Oxygenase-1 and miR-378 Affects Non-Small Cell Lung Carcinoma Growth, Vascularization, and Metastasis

Abstract: Aims: Heme oxygenase-1 (HO-1, HMOX1) can prevent tumor initiation; while in various tumors, it has been demonstrated to promote growth, angiogenesis, and metastasis. Here, we investigated whether HMOX1 can modulate microRNAs (miRNAs) and regulate human non-small cell lung carcinoma (NSCLC) development. Results: Stable HMOX1 overexpression in NSCLC NCI-H292 cells up-regulated tumor-suppressive miRNAs, whereas it significantly diminished the expression of oncomirs and angiomirs. The most potently down-regulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
140
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(153 citation statements)
references
References 58 publications
12
140
1
Order By: Relevance
“…One study reported increased levels of miR-378 in the serum of patients with ccRCC (20) and another study reported overexpression of miR-378 in human non-small cell lung carcinoma and an association of expression with enhanced tumor proliferation and migration (26). However, in the present study, miR-378 levels were lower in tumor samples than in normal tissues.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…One study reported increased levels of miR-378 in the serum of patients with ccRCC (20) and another study reported overexpression of miR-378 in human non-small cell lung carcinoma and an association of expression with enhanced tumor proliferation and migration (26). However, in the present study, miR-378 levels were lower in tumor samples than in normal tissues.…”
Section: Discussioncontrasting
confidence: 79%
“…Our results are also consistent with the report of Redova et al (25) who found that more miRNAs were downregulated in ccRCC tissues than in normal tissues (73 of 78 miRNAs). Notably, several studies of non-small cell lung cancer (NSCLC) have also indicated an important role for miR-378 in tumor progression and angiogenesis (26,27). This miRNA appears to target the tumor suppressors Sufu and Fus-1 (28).…”
Section: Discussionmentioning
confidence: 99%
“…The binding interaction causes translational inhibition and/or mRNA degradation [7]. Moreover, dysregulation of miRNAs expression may contribute to tumorigenesis by inhibiting the expression of tumor suppressor genes or promoting the expression of proto-oncogenes [8]. Several studies have demonstrated that miRNAs have high stability in human serum or plasma due to protection from RNases [9][10][11], suggesting their potential use as diagnostic biomarkers.…”
Section: Introductionmentioning
confidence: 99%
“…For example, miR-377 and miR-217 can decrease HO-1 expression in endothelial cells by a direct interaction with the 3= untranslated region (UTR) of HO-1 mRNA (29), whereas miR-378 decreases HO-1 expression in lung cancer cells (30). We hypothesized that there may also be miRNAs targeting HO-1 in PRRSV-permissive cells, which may subsequently affect the regulation of PRRSV replication.…”
mentioning
confidence: 99%